2020
DOI: 10.32674/jis.v10is(2).2713
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Well-Being of Newly-Arrived Indonesian Students in Taiwan

Abstract: A study abroad program is of great interest among high school leavers globally. Indonesian school leavers are no exception. This study investigates the psychological well-being of Indonesian students studying at Taiwanese universities. Informed by a phenomenological approach, sixteen Indonesian participants who studied in Taiwan were recruited for this case study. Data were garnered from semi-structured interviews and observations. The findings of the study show that the students were unable to manage their em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…The results showed that 32% of students had a high (26%) to very high (6%) levels of psychological well-being, 36% had a moderate level of psychological well-being, and 32% had a low (25%) to very low (7 %) levels of psychological well-being. These results were in line with the research by Kurniasari et al (2019), Rahman et al (2020), andSimanjuntak et al (2021) that found that the psychological well-being of students tends to be low and very low. This level is caused by the ability to adapt to prevailing values and new situations encountered, which can create a sense of loneliness and an inability to manage emotions, especially in completing the final projects, leading to psychological disorders in individuals when unable to adapt to the situation experienced.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that 32% of students had a high (26%) to very high (6%) levels of psychological well-being, 36% had a moderate level of psychological well-being, and 32% had a low (25%) to very low (7 %) levels of psychological well-being. These results were in line with the research by Kurniasari et al (2019), Rahman et al (2020), andSimanjuntak et al (2021) that found that the psychological well-being of students tends to be low and very low. This level is caused by the ability to adapt to prevailing values and new situations encountered, which can create a sense of loneliness and an inability to manage emotions, especially in completing the final projects, leading to psychological disorders in individuals when unable to adapt to the situation experienced.…”
Section: Discussionsupporting
confidence: 92%
“…However, prior research has yielded conflicting results about the impact of online physical education classes, with some studies highlighting negative consequences such as unreliable internet connections and expensive data limitations . Furthermore, it should be noted that the advent of online learning has had a significant impact on individuals' psychological well-being, as evidenced by previous research (Rahman, Hamka & Lin, 2020;Teresa, Guss & Boyd, 2021;Ahmad, Ismail & Husain, 2022). This, in turn, has been found to have an indirect effect on elite students' academic achievement, leading to a steady deterioration (Hashemi, 2021;Yuda et al, 2022).…”
Section: Introductionmentioning
confidence: 85%
“…Psychological well-being was the second factor estimated to predict elite student-athletes academic achievement. Psychological well-being was conceptualised as the ability to develop potential independently and determine life goals in a more positive direction (Muqodas et al, 2020;Rahman, Hamka & Lin, 2020;Li, 2021). According to Ku-Johari, Bali-Mahomed, Mahmud, Amat & Saadon (2022), psychological well-being is welfare that is free from negative feelings and turns into positive ones.…”
Section: Introductionmentioning
confidence: 99%
“…This viewpoint contributes to interpreting the experience of international students in dealing with new situations as international students experience an additional complex challenge due to new policies from local governments that affect the learning system and social life routines. For example, the study by Rahman & Lin (2020) reported the psychological well-being of new Indonesian students studying in Taiwan from the social, educational, and cultural dimensions. The main findings show that preparation and social support from the surroundings are needed to reduce the possibility of psychological problems such as stress and disengagement faced by international students studying in a foreign country.…”
Section: Discussion Of Findingsmentioning
confidence: 99%